Mobile Gamma Cameras and 99mTc-Labelled Phosphates in Acute Myocardial Infarction - Pereira-Prestes, A. V.; Donaldson, R. M.; Ell, P. J.; Brown, N. J. G.; Jarritt, P. H.; Al-Baghdadi, T.; Elliott, A. T. (Nuklearmedizin - NuclearMedicine, 1979)
99mTc-labelled phosphates (PyP, IDP and MDP) were compared for their usefulness for the diagnosis of myocardial infarction. The results indicated the superiority of 99mTc-labelled imidodiphosphonate over the other 99mTc-labelled phosphates. At the same time, two mobile gamma cameras were compared with respect to their instrumental characteristics and clinical versatility and their advantages and disadvantages are reported.